Buccal fat pad anatomy and its importance for safe clinical procedures: A Review - Ferreira, Beatriz Carmona; Watanabe, Luciane Naomi Oguma; Freire, Alexandre Rodrigues; Botacin, Paulo Roberto [UNESP]; Prado, Felippe Bevilacqua; Rossi, Ana Cláudia (The Brazilian Society of Anatomy (SBA), 2021)
Introduction: clinical applications of the buccal fat pad have been reported more frequently in recent years, mainly in Dentistry area. The aim of this study was to review the literature identifying the anatomy of the buccal fat pad, including its development, functional importance and some of its applications in different clinical procedures. Review: one electronic research database, PubMed, was investigated using the following restricted keywords: buccal fat pad, anatomy and clinical procedures. Forty-nine articles were found. The final review included thirty-three of them. Publications identified were considered between February 1989 and December 2020. Conclusion: this review showed that the buccal fat pad is a complex anatomical structure that has essential functions and can be applied to different clinical approaches. It is indispensable for the professionals who work with this structure to know it in detail so to obtain success on the procedures involving the buccal fat pad.
Keywords: Adipose tissue; Anatomy; Buccal fat pad; Clinical procedures